Psychological Resilience and Emotional Regulation and Their ‎Relationship to Coping Strategies of Stressful Life Events among ‎Sudanese University Students - Alawad, Nawal AbdElgadir Hassan (Dirasat: Educational Sciences, 2025)
Objectives: The present study seeks to examine the levels of psychological resilience and emotional regulation among Sudanese university students, and to explore the relationship of these two variables with strategies employed for coping with stressful life events. Methods: To address the research objectives, the study utilized three standardized instruments: the Psychological Resilience Scale (Mampane, 2010), the Emotion Regulation Questionnaire (Gross & John, 2003), and the Coping Strategies Scale for Stressful Life Events (Taha, 2020). The sample comprised 560 undergraduate students enrolled in various Sudanese universities, selected through appropriate sampling procedures. Results: The findings revealed that participants demonstrated high levels of psychological resilience, emotional regulation, and usage of coping strategies in response to stressful life events. Furthermore, a significant positive correlation was identified between psychological resilience and both emotional regulation and coping strategies. A similar positive association was observed between emotional regulation and coping strategies. No statistically significant differences were found in psychological resilience based on demographic variables. However, emotional regulation varied significantly by gender, favoring male students, and by university type, with students from public institutions exhibiting higher regulation levels. Additionally, psychological resilience and emotional regulation together accounted for 27.4% of the variance in coping strategies. Conclusion: The study underscores the importance of psychological resilience and emotional regulation in managing stress among university students. It recommends further empirical investigations considering additional demographic variables such as academic discipline, year of study, residential status, and family income.